On the relationships between auditory and visual factors in a residential environment context: A SEM approach - Garzón, Luis; Bravo-Moncayo, Luis; Arellana, Julián; Ortúzar, Juan de Dios (Frontiers in Psychology, 2023)
To understand the effects of specific elements that may enhance or detract residents’ well-being, it is important to explore the relationships between auditory and visual factors, based on people’s sensory experiences. Although residential environments provide natural experimental conditions to observe these relationships, the complexity of measuring sensory perceptions and their subsequent interpretation constitutes a challenge. This study aims to identify the influence of socio-demographics and residential location characteristics on three latent variables: noise-Sensitivity, sound-Pleasantness, and visual-Liveability in a Latin American city. The methodology is replicable and relies on a digital survey that displays environments in 360-format video and uses sound immersion techniques; it was applied to a sample of household heads in Quito, Ecuador. Based on an efficient experimental design, we selected different residential environments according to acoustic-visual attributes and the proximity to residential, commercial, and recreational land uses. Structural Equation Models (SEM) were estimated using mediating variables. Our results reveal the influence of noise-Sensitivity on sound-Pleasantness and, indirectly, on visual-Liveability. Further analysis shows that the impact of sound and visual perception changes with different socio-demographics and residential location characteristics.